Changes in the pharmacokinetics of lurasidone in a pregnant woman with schizophrenia - Mihoko Kawai; Ryosuke Aratake; Tadashi Ogawa (PCN Reports)
Abstract Background The population of pregnant women with schizophrenia is increasing. Managing schizophrenia during pregnancy poses unique challenges due to the potential effects of second‐generation antipsychotics on maternal mental health and fetal development and changes in drug pharmacokinetics. Evidence on how physiological changes during pregnancy affect the levels of second‐generation antipsychotics, particularly lurasidone, is limited. There are no data on effectively managing medications and decreasing side‐effects during pregnancy. Case Presentation We presented the case of a 34‐year‐old pregnant woman with schizophrenia who had a stable condition with lurasidone therapy before conception. However, she exhibited worsening psychiatric symptoms during the third trimester of pregnancy. Serial measurements of serum lurasidone levels were performed during late pregnancy. Despite maintaining the same dosage, her serum lurasidone levels significantly decreased during the third trimester (maximum decrease of ~65% compared with baseline) and rapidly increased during the postpartum period, coinciding with an improvement in psychiatric symptoms. Conclusion Decreased serum lurasidone levels during pregnancy may increase the risk of symptom worsening in patients with schizophrenia. Hence, clinicians should be knowledgeable about the risk of decreased drug levels and the need for therapeutic monitoring and dosage adjustments during pregnancy to maintain treatment efficacy and maternal and fetal health.